The global burden of musculoskeletal conditions for 2010: an overview of methods. Issue 6 (18th February 2014) - Hoy, Damian G; Smith, Emma; Cross, Marita; Sanchez-Riera, Lidia; Buchbinder, Rachelle; Blyth, Fiona M; Brooks, Peter; Woolf, Anthony D; Osborne, Richard H; Fransen, Marlene; Driscoll, Tim; Vos, Theo; et al.
Abstract : The objective of this paper is to provide an overview of methods used for estimating the burden from musculoskeletal (MSK) conditions in the Global Burden of Diseases 2010 study. It should be read in conjunction with the disease-specific MSK papers published in Annals of Rheumatic Diseases . Burden estimates (disability-adjusted life years (DALYs)) were made for five specific MSK conditions: hip and/or knee osteoarthritis (OA), low back pain (LBP), rheumatoid arthritis (RA), gout and neck pain, and an 'other MSK conditions' category. For each condition, the main disabling sequelae were identified and disability weights (DW) were derived based on short lay descriptions. Mortality (years of life lost (YLLs)) was estimated for RA and the rest category of 'other MSK', which includes a wide range of conditions such as systemic lupus erythematosus, other autoimmune diseases and osteomyelitis. A series of systematic reviews were conducted to determine the prevalence, incidence, remission, duration and mortality risk of each condition. A Bayesian meta-regression method was used to pool available data and to predict prevalence values for regions with no or scarce data. The DWs were applied to prevalence values for 1990, 2005 and 2010 to derive years lived with disability. These were added to YLLs to quantify overall burden (DALYs) for each condition. To estimate the burden of MSK disease arising from risk factors, population attributable fractions were determined for bone mineral density as a risk factor for fractures, the occupational risk of LBP and elevated body mass index as a risk factor for LBP and OA. Burden of Disease studies provide pivotal guidance for governments when determining health priority areas and allocating resources. Rigorous methods were used to derive the increasing global burden of MSK conditions.